2021
DOI: 10.1155/2021/5536884
|View full text |Cite
|
Sign up to set email alerts
|

EEWMP: An IoT-Based Energy-Efficient Water Management Platform for Smart Irrigation

Abstract: Precision agriculture is now essential in today’s world, especially for countries with limited water resources, fertile land, and enormous population. Smart irrigation systems can help countries efficiently utilize fresh water and use the excess water for barren lands. Smart water management platform (SWAMP) is an IoT-based smart irrigation project designed for efficient freshwater utilization in agriculture. The primary aim of SWAMP is to auto manage water reserves, distribution, and consumption of various le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The precision irrigation systems could be used to control the changing environmental circumstances in an adaptive manner. Various machine learning applications have been studied in literature, namely crop management [72] , livestock management [88] , water management [89] and soil management [46] .…”
Section: Use Of Iot and Big Data For Optimisation Of Irrigation Systemsmentioning
confidence: 99%
“…The precision irrigation systems could be used to control the changing environmental circumstances in an adaptive manner. Various machine learning applications have been studied in literature, namely crop management [72] , livestock management [88] , water management [89] and soil management [46] .…”
Section: Use Of Iot and Big Data For Optimisation Of Irrigation Systemsmentioning
confidence: 99%
“…242 For example, smart water management platform (SWAMP) is an IoT-based irrigation project designed to automatically manage water reserves, distribution, and consumption, and avoid overirrigation/under-irrigation, which has improved energy-efficient water management by 30%. 243 6.2. Sensor Data Processing/Control.…”
Section: Future Perspective Of Rtcsm Technologymentioning
confidence: 99%
“…In terms of sensor networks, sensor array consisting of multiple pieces of low-cost miniature sensors connected with Internet of Things (IoT) can be deployed to collect and exchange multiple types of sensor data, boost sensor-to-sensor communication, and make optimal decisions but with less human interaction . For example, smart water management platform (SWAMP) is an IoT-based irrigation project designed to automatically manage water reserves, distribution, and consumption, and avoid over-irrigation/under-irrigation, which has improved energy-efficient water management by 30% …”
Section: Future Perspective Of Rtcsm Technologymentioning
confidence: 99%
“…The authors of [28] indicated that the increase in power consumption due to the integration of the proposed Blockchain architecture required additional 6% of energy as compared to classical systems that operate without the Blockchain inclusion; however such a system provides trusted sensing devices over public Blockchain networks. A smart irrigation system was proposed in [30] to be suitable for drip, sprinkler ,surface ,and lateral irrigation models.…”
Section: A Agricultural (Irrigation)mentioning
confidence: 99%